Ultrasound Velocity Measurements in High-Chromium Steel Under Plastic Deformation; IOP Conference Series: Materials Science and Engineering; Vol. 125 : Materials Treatment: Current Problems and Solutions - Lunev A. G. Alexey Gennadievich; Bochkareva A. V. Anna Valentinovna; Barannikova S. Svetlana; Zuev L. Lev (2016, 2016)
Title screen